2014
DOI: 10.1063/1.4890022
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent spectrum study of a quantum dot single-photon detector based on resonant tunneling effect with near-infrared response

Abstract: We present the photocurrent spectrum study of a quantum dot (QD) single-photon detector using a reset technique which eliminates the QD's “memory effect.” By applying a proper reset frequency and keeping the detector in linear-response region, the detector's responses to different monochromatic light are resolved which reflects different detection efficiencies. We find the reset photocurrent tails up to 1.3 μm wavelength and near-infrared (∼1100 nm) single-photon sensitivity is demonstrated due to interband tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…If the illumination is turned off, the current drops a little but still keeps in a high level compares to the dark level. In other words, the photodetector can "memorize" electrons and holes, which is the so-called "memory effect" [3][4][5]. The high photosensitivity of detector indicates a long dwell time (τ d > 1 s) of a photoexcited hole following capture at one of the dots.…”
Section: Sensitivity Of Photodetectormentioning
confidence: 99%
See 1 more Smart Citation
“…If the illumination is turned off, the current drops a little but still keeps in a high level compares to the dark level. In other words, the photodetector can "memorize" electrons and holes, which is the so-called "memory effect" [3][4][5]. The high photosensitivity of detector indicates a long dwell time (τ d > 1 s) of a photoexcited hole following capture at one of the dots.…”
Section: Sensitivity Of Photodetectormentioning
confidence: 99%
“…This is a particular problem for SPADs designed for IR sensitivity [1][2][3][4]. It has been shown that QD-RTD (quantum dots resonant tunneling diodes) modified to contain a layer of quantum dots can detect single photons at temperatures up to 77 K [4][5][6]. These detectors rely on sensing the electrostatic charge of single photoexcited carriers trapped on the dots.…”
Section: Introductionmentioning
confidence: 99%
“…При использовании различных комбинаций потенциаль-ных барьеров, квантовых ям и(или) слоев квантовых точек благодаря эффектам туннелирования и кванто-вания движения носителей в области с собственной проводимостью (i-область) гетероструктуры оказалась возможной тонкая настройка динамики захвата и ре-комбинации, что привело к новым приложениям в фотонике и элементной базе квантовых вычислений. Например, p−i−n-гетероструктуры были использованы как в качестве одиночных излучателей фотонов, так и как чувствительные фотоприемники [1][2][3][4], в кото-рых один фотовозбужденный носитель, локализован-ный в квантовой яме или на квантовой точке, может производить значительные изменения в проводимости устройства. Физика фотовозбужденных носителей в этом типе полупроводниковых гетероструктур, следователь-но, имеет не только фундаментальный интерес, но и востребована в целом ряде разнообразных практических приложений.…”
unclassified
“…1. Introduction: Electron transfer (ET) from valence to conduction band states in semiconductors is the basis of modern electronics [1][2][3][4][5]. The fundamental process of ET is central to many light-driven reactions.…”
mentioning
confidence: 99%